Stanovení barbiturátů z biologického materiálu - Pracharová, M; Pestálovă, M; Dubský, H; Hána, K (Soudni lekarstvi, 1975)
A trace quantitative analysis of barbiturates has been carried out in blood, urine, organs and in gastric and intestinal concents. The amount of sample required for analysis is very small [approximately 400 mul blood]. Extraction is carried out four times with the mixture of acetone and either 1:1]. The preparation of columns, packing and standards has been described. The device used for the analyses [Chrom 3] is furnished with an adjusted feeding block preventing the decomposition of samples in the doser. The column temperature is 190 degrees C, the column packing is Chromaton N-AW-DMCS coated with 3% NPGS and 0.75% trimer acid, detector FID.
Keywords: soudní lékařství; amobarbital; barbituráty; koncentrace vodíkových iontů; chromatografie plynová; pentobarbital; Amobarbital; Barbital; Forensic Medicine; Humans; Hydrogen-Ion Concentration; barbital; Pentobarbital; Chromatography, Gas; hexobarbital; fenobarbital; Phenobarbital; Barbiturates; lidé; Hexobarbital